(untitled) (Management and Connections Journal, 2024)
Emotion is addressed relatively frequently in studies on entrepreneurship. However, research is still fragmented, dispersed and poorly aligned with the conceptions of emotion produced in the fields of Sociology, Anthropology and Organizational Studies. This article aims to integrate and discuss knowledge about emotions for entrepreneurship, providing greater alignment with the conception of emotion as sociocultural dynamics. Although research points to the importance of sociocultural dynamics on emotions, we have not yet applied this knowledge in greater depth to the context of entrepreneurship. The research results contribute to the advancement of knowledge in the field of entrepreneurship by providing an integrated and consolidated view of academic production on emotions and by proposing and discussing the sociocultural dynamics of emotion as a perspective to theoretically renew future research.